NRIC 2016: 10 YEARS ON, STILL GOING STRONG - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 August 2016 The ever popular and prestigious Novel Research and Innovation Competition (NRIC) 2016 organised by the Students’ Representatives Council, Universiti Sains Malaysia (USM) for the 10 year running has been boosted with 101 projects and 404 participants competing, including those from neighbouring countries and India.